A Rare Case of Compressive Cervical Myelopathy Presenting with Reversible Complete Heart Block (GAIMS Journal of Medical Sciences, 2023)
We present here a rare case of an elderly male who presented with the complaints of progressively worsening gait imbalance, associated with acute onset giddiness. On evaluation, the patient had bradycardia with exaggerated upper and lower limb deep tendon reflexes and pain on neck movements. A Magnetic Resonance Imaging (MRI) showed posterior disc herniations at C6-C7 level with neural foraminal narrowing, and 12 lead Electrocardiogram showed Complete Heart Block (CHB). Decompressive surgery with temporary pacing was done, following which, the patient recovered well. Although Permanent Pacemaker (PPM) was initially planned, it was not required due to reversion to normal sinus rhythm on ECG, post-surgery. Hence, rare reversible causes of CHB should be ruled out, before opting for a long term permanent invasive treatment modality.